(untitled) (International Seven Journal of Multidisciplinary, 2025)
Access to bank credit is essential for the development and sustainability of both individual and business financial goals. However, obtaining favorable loan conditions requires more than eligibility—it demands strategic negotiation based on creditworthiness, preparation, and knowledge of market dynamics. This article examines evidence-based strategies for negotiating interest rates and payment terms with banks, emphasizing the importance of maintaining a positive credit history, presenting a well-structured business plan, and cultivating long-term banking relationships. Drawing from the academic literature on credit access, relationship banking, and financial transparency, the study highlights how informed borrowers can leverage timing, competition, and legal clarity to secure more advantageous terms. Effective negotiation with financial institutions is not merely a transactional act, but a strategic tool for enhancing long-term financial resilience and growth.